IDENTIFICATION OF ARBUSCULAR MYCORRHIZAL FUNGI IN RHIZOSPHERE SOIL OF SEVERAL GRASS SPECIES AND CACAO (Theobroma cacao L.) BASED ON ITS SPORE MORPHOLOGICAL CHARACTERISTICS - Sintya Dewi, Ni Kadek; Susrama, I Gede Ketut; Sritamin, Made; Adnyana, Made; Wirawan, I Gede Putu (International Journal of Biosciences and Biotechnology; Vol 2 No 1 (2014), 2014)
Arbuscular mycorrhizal fungi live in a symbiotic mutualism with plant roots and helps plant absorbnutrients and also able to live in various places. The study aimed to identify arbuscular mycorrhizal fungiin rizhosphere of several grass and cacao through microscopic method based on morphologicalcharacteristics and was conducted from December 2013 to March 2014. The methods used in this studywere spore isolation using wet sieving and root staining techniques. The results showed that arbuscularmycorrhizal fungi spores found in Imperata cylindrica L. were spores of Glomus (Glomales: Glomeaceae)with its vesicular and hyphae structure. The presence of spores and structures in Paspalum notatum wereAcaulospora (Glomales: Acaulosporaceae) and Gigaspora with its arbuscules, vesicules and hyphae structure.Spores and structures found in the Pennisetum purpureum were belong to genus of Glomus with hyphaeand arbuscular structure. Spores and structures of mycorrhizal fungi in Cyperus rotundus are spores of thegenus of Gigaspora (Glomales: Gigasporineae) and spores of Glomus with internal hyphae structure. Whilespores and mycorrhizal structures in Cacao were found two types of spore belong to genus of Glomus withhyphae and vesicular structures.
Keywords: Glomus, Gigaspora, Acaulospora, Arbuscular Mycorrhiza Structure